Hubungan Sosial Media Addiction dengan Motivasi Belajar pada Mahasiswa - Kartasasmita, Sandy; Shofiyanti, Ghina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research illustrates the substantial growth in the number of internet users and social media users in Indonesia and its implications for student learning encouragement. With a focus on the increasing dependence on technology, this study sought to investigate the correlation between the level of dependence on social media, also known as dependence on social media and the level of learning motivation among university students. The quantitative method was applied by conducting a survey of 101 students using a questionnaire that had gone through a validity and reliability process. The results of data analysis using the SPSS statistical tool show that there is a significant positive relationship between the level of dependence on social media and student learning motivation. However, around 35.2% of the variation in the level of learning motivation cannot be explained by the factor of dependence on social media, indicating the possibility of other factors influencing learning motivation. The implications of these findings emphasize the importance of careful understanding and wise management of the use of social media in maintaining and maintaining student learning motivation. Practical recommendations include effective guidance for students in the use of technology and self-control in interacting with social media. Theoretically, research suggests adding variables for further studies that can provide a more comprehensive understanding of the factors that influence learning motivation.